Hyperbole Expression in â€œCinderellaâ€ 2021 Selected Soundtrack Songs - Munte, Martua; Afriana, Afriana (Institut Agama Islam Negeri Palopo, 2023)
Hyperbole is a figure of speech that is commonly used in a range of literary works, as well as in ordinary English. A figure of speech that exaggerates a setting or situation in a remark. One of them appears in the song's lyrics. Songwriters utilize hyperbolic language to convey meaning to listeners, making the message more profound and emotive. The goal of this study was to determine how often the song writers used hyperbole in six selected soundtracks from the movie of Cinderella 2021. In addition, the researcher also analyzed the types of meaning contained in each song lyric which indicated hyperbole based on Leech'theory. This study conducted a qualitative method using referential equivalent techniques in describing hyperbole and its types of meaning that the authors found proposed by Sudaryanto. The researcher found 17 data containing hyperbolic expressions in the six selected soundtrack songs in the movie of Cinderella 2021. The songs that contain the most hyperbolic expressions are found in two song titles entitled â€œSomebody To Love